THE EFFECT OF MENTAWAI BEACH SAND AS A SUBSTITUTE FOR RIVER SAND ON THE COMPRESSIVE STRENGTH OF CONCRETE - A, Arman.; Mulyati, Mulyati; Fajar, Fajar; Roza, Angelalia; Marizal, Yoharis (Ensiklopedia of Journal, 2025)
The Concrete technology innovation is always required to answer the challenges of the need for the resulting concrete to be of high quality including strength and durability without ignoring economic value. One of the additional materials can be using pumice for fine aggregate. In such conditions, it is possible that the need for quality fine aggregates will be difficult to fulfill. The aim of this research is to determine the effect of variations in the use of sea sand on the compressive strength of concrete. This research is experimental in nature and was carried out in the Civil Engineering laboratory of the Padang Institute of Technology (ITP). Standard regulations for concrete mixing specifications use SNI 7656-2012 which concerns "procedures for selecting mixtures for normal concrete, heavy concrete and mass concrete".  Therefore, this research aims to determine the effect of using beach sand as a substitute for river sand on the compressive strength of concrete. In this research, the additional material used was Mentawai beach sand with percentages of 0%, 20%, 40%, 60% and 80% at 28 days with 3 samples for each percentage. The test object used was a steel cylinder with a diameter of 15 cm and a height of 30 cm. The quality of the concrete used is fc' 20.75 Mpa. The research results showed that the compressive strength value of the concrete in the Trial Mix was 35.52 MPa, while at 28 days of concrete age, the compressive strength value reached 22.21 MPa, in accordance with the planned target of 20.75 MPa. Meanwhile, with a 20% variation, the compressive strength value was 19.73 MPa, and experienced a decrease of 11.16% compared to normal concrete. With a 40% variation, the compressive strength value was 18.11 MPa and decreased by 18.46% compared to normal concrete. At 60% variation, the compressive strength value was 16.75 MPa and decreased by 24.58% compared to normal concrete. At 80% variation, the concrete compressive strength value was 13.98 MPa and decreased by 37.05%. Keywords: Concrete, Beach sand, Compressive strength.